Syncope and hypotension associated with carotid sinus hypersensitivity in a patient with nasopharyngeal carcinoma: A case report. Issue 37 (September 2018) - Zhang, Shuting; Wei, Chenchen; Zhang, Mingming; Su, Minggang; He, Sen; He, Yong
Abstract: Rationale: Carotid sinus hypersensitivity (CSH) is traditionally classified into 3 subgroups: cardioinhibitory, vasodepressor, and mixed subtypes. However, the underlying mechanism of CSH in head and neck cancer is controversial. Several pathological mechanisms of CSH have been proposed: atherosclerotic noncompliance, sternocleidomastoid proprioceptive denervation, and generalized autonomic dysfunction. Patient concerns: We reported a 75-year-old man who had recurrent syncope attacks secondary to hypotension and reduced plasma norepinephrine (NE) levels. CSH was suspected when carotid massage induced syncope-like symptom. Diagnoses: Nasopharynx carcinoma with regional lymph node involvement and CSH. Interventions: On admission, dopamine was administered to maintain the blood pressure. When NE deficiency was confirmed, intravenous NE combined with oral midodrine replaced the dopamine treatment. Outcomes: The syncopal episodes completely resolved with periodic occurrence of hypertension. Lessons: Our case suggests a potential role of carotid sinus in regulating the release of NE in adrenal gland and that the monitoring of catecholamine level is recommended in the CSH cases either from head and neck tumors or other mechanical manipulation of carotid sinus.